Generation A : perspectives on special populations and international research on autism in the workplace - Hurley-Hanson, Amy E.; Giannantonio, Cristina M. (Emerald studies in workplace neurodiversity, 2022)
Providing several new contributions to both the disabilities literature and research on special populations and international perspectives on Generation A, this book explores ways that researchers can help facilitate finding and maintaining employment for individuals with Autism Spectrum Disorder (ASD). The chapters included in this volume are organized and presented along two themes. The first theme, Special Populations Affected by Generation A, explores the experiences of special populations within the generational cohort of Generation A. Chapters in this section of the book explore the growth of STEM occupations and how this growth may create opportunities for the women of Generation A. Other chapters in this section examine the career and life effects of being a parent of a young adult with ASD, the role of allies in supporting the efforts of young adults with ASD to find and maintain successful employment, and the unique career experiences of individuals with ASD in the legal profession. The second theme, International Research on Generation A, explores the experiences of Generation A from an international perspective. The countries represented are India, Great Britain, Ireland, and Trinidad and Tobago. These chapters explore various ways that individuals with ASD and members of Generation A are being included in organizations in these countries. The legal issues associated with hiring individuals with ASD, as well as efforts by Non-Governmental Organizations (NGOs) to facilitate their employment, are also presented.